Analysis Of The Physicochemical Properties Of The Processed Fruits And Vegetable Products - MEETU CHAUDHARY; SUSHEEL K. VERMA (International Journal of Pharma and Bio Sciences, 2011)
Fruits and vegetable products are processed because raw fruits and vegetables products are very soon contaminated and so these are processed in large scale without any contamination and could be eaten many times. Processed foods such as tomato juice, jam, pickle, orange juice were taken and their moisture, ash content, protein, fat content and calorific values were estimated and found no loss in the above contents in these food products.